2020
DOI: 10.1097/hjh.0000000000002371
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ambulatory SBP and overweight on executive function performance in children and adolescents

Abstract: Background and aim: Neurocognitive impairment has recently emerged as a hypertensive target organ damage in children and adolescents. In the present study, we aimed to examine the effect of hypertension and overweight on executive function performance in youth. Methods: The study population included 116 consecutive children and adolescents referred to our outpatient hypertension clinic who underwent ambulatory blood pressure monitoring (ABPM) and assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…There is growing number of epidemiological studies to explore the associations between the individual or multiple components of the cardiovascular health and executive function in children. Poor diet, physical inactivity, obesity, and hypertension have each been shown to be associated with deficits in the executive function performance in children (9)(10)(11). The metabolic syndrome, characterized by a constellation of metabolic and anthropometric traits, such as abdominal obesity, hypertension, dyslipidemia, and hyperglycemia, has been reported to negatively impact the executive function in children (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing number of epidemiological studies to explore the associations between the individual or multiple components of the cardiovascular health and executive function in children. Poor diet, physical inactivity, obesity, and hypertension have each been shown to be associated with deficits in the executive function performance in children (9)(10)(11). The metabolic syndrome, characterized by a constellation of metabolic and anthropometric traits, such as abdominal obesity, hypertension, dyslipidemia, and hyperglycemia, has been reported to negatively impact the executive function in children (31).…”
Section: Discussionmentioning
confidence: 99%
“…These high-order skills of executive function develop dramatically across childhood and were related to learning and academic achievement as well as life quality in adulthood (7,8). Many epidemiological studies have explored the relationship between poor diet, physical inactivity, obesity, and hypertension, individually or in various combination, with deficits in the domain of executive function in children, albeit the inconsistent results exist (9)(10)(11). Moreover, they mainly focused on either fewer metrics or individual risk factor, evidence concerning the association between the AHA-defined clusters of cardiovascular health metrics with executive function is still sparse.…”
Section: Introductionmentioning
confidence: 99%
“…28 Determining the influence of UA in cognition is complicated by the fact that both serum UA levels and hypertension are associated with kidney function, obesity, and other common cardiometabolic factors. Children and adolescents with primary hypertension are more likely to have several cardio-metabolic risk factors, but also are at higher risk of worse executive performance compared with normotensive children or healthy controls, 8 and thus, could be a target population to study the impact of serum UA on cognitive function in youth. In 6036 adolescents from the 1999 to 2006 National Health and Nutrition Examination Survey, participants with a UA level ≥5.5 mg/dL had 2.03 times higher odds of having elevated BP compared with those with serum uric acid <5.5 mg/ dL.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work suggested that obesity may increase the risk of EF issues in children and adolescents [8].However, the weight-EF relationship in adolescents has not been well studied. While some studies reported adolescents with overweight/obesity had poor EF performance [9], others showed null results [10,11]. Additionally, few research has investigated the association of underweight and EF in…”
mentioning
confidence: 99%
“…Adolescents with weight concerns may tend to experience negative self-image and more maladaptive behaviors (e.g., unhealthy eating, physical inactivity, and more screen exposure) and, in turn EF problems [15], alternatively, negative emotions may serve to exacerbate the weight issue [16], which gave us a hint that negative emotions might moderate the weight-EF relationship. However, much of the current literature only focused on the solitary effect of weight status on EF without considering moderating effect of negative emotions [9][10][11]. Given that a growing number of adolescents suffer from weight problems, it is crucial to identify modi able targets for the EF improvement.…”
mentioning
confidence: 99%